2012
DOI: 10.1097/ta.0b013e31824d68bd
|View full text |Cite
|
Sign up to set email alerts
|

Remote inflammatory response in liver is dependent on the segmental level of spinal cord injury

Abstract: Our findings indicate that traumatic SCI triggers an acute SIR that contributes to hepatocellular injury. SCI-induced remote injury/dysfunction to the liver appears to be transient and is more robust after an upper thoracic SCI compared with a lower thoracic SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…SCI at cervical and high thoracic levels is known to trigger a severe systemic inflammatory response 20 , but the role of inflammation in complete spinal transection at the mid-thoracic-level and the secondary voiding dysfunction was not investigated so far. An earlier study on SCI patients 18 identified IL-6, CXCL-1, and CCL2 as potential serum biomarkers for SCI.…”
Section: Discussionmentioning
confidence: 99%
“…SCI at cervical and high thoracic levels is known to trigger a severe systemic inflammatory response 20 , but the role of inflammation in complete spinal transection at the mid-thoracic-level and the secondary voiding dysfunction was not investigated so far. An earlier study on SCI patients 18 identified IL-6, CXCL-1, and CCL2 as potential serum biomarkers for SCI.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Data in Figure 1 show that activated Kupffer cells, the resident hepatic macrophages, persist at and beyond 1 dpi in liver. Indeed, hepatic CD68 mRNA increased > 100-fold by 1 dpi and remained at that level for at least 21 dpi (Fig.…”
Section: Thoracic Sci Induces Robust Liver Inflammation and Lipid Accmentioning
confidence: 99%
“…SCI initiates a systemic inflammatory response defined by rapid elevation of chemokines and leukocytes in the circulation, lungs, kidneys, and liver, which evokes local tissue pathology such as edema and bleeding. [1][2][3][4][5][6] This systemic response in turn likely contributes to acute and possibly chronic dysfunction in patients with SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that SCI causes local and systemic inflammatory responses which are associated with the production of free radicals (18)(19)(20). Free radical-induced lipid peroxidation is one of the mechanisms of the secondary spinal cord injury which result in an autodestructive phenomenon of spinal cord (21).…”
Section: Discussionmentioning
confidence: 99%